Research related to fireflies (Coleoptera: Lampyridae) around the world over the year 2000 – 2021 : an overview and guidelines - Muhammad Fakruhayat Ab Rashid,; Azimah Abd Rahman,; Siti Masayu Rosliah Abdul Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fireflies are groups of the Coleoptera order and the Lampyridae family. Fireflies are typically classified as nocturnal insects, however some are diurnal, and others have mixed nocturnal and diurnal characteristics. They are also known as luminescent insects due to their ability to emit light. Bibliometric analysis is a popular and rigorous method for discovering and analyzing enormous volumes of scientific data. Therefore, the objective of this study is to present overview and guidelines in studies related to firefly research worldwide from 2000 to 2021 using bibliometric analysis to provide researchers and scholars around the world an overview of results and trends in firefly research. A textual query on three databases; Scopus (289 papers), Web of Science (303 papers), and PubMed (541 papers) using the term “Fireflies Coleoptera Lampyridae” was performed on 30 August 2021 retrieving 1133 scholarly papers from 2000 to 2021 related to firefly studies for in-depth analysis. Bibliometric analysis were performed using Rstudio software version 4.1.1 and biblioshiniy for bibliometrix to visualize and analyze trends of firefly research. This bibliometric analysis was analyzed the annual scientific publication growth, the most productive authors, most frequent word has been using, most famous journal name, and which countries has highest collaboration with other country in firefly research. According to the findings of the analysis, there is significant inconsistency in global trends in annual scientific production, with the number of publications increasing and decreasing. In firefly research, according to the findings has show the most relevant authors is Fu X (Scopus), Fu XH (WoS), and Hosseinkhani S (PubMed). Moreover, the most relevant journals articles in fireflies studies is Zootaxa (Scopus & WoS), and Photochemical & Photobiological Sciences : Official Journal Of The European Photochemistry Association And The European Society For Photobiology (PubMed). Futhermore, the most frequently utilized keywords in fireflies study is lampyridae, firefly, bioluminescence, animals and fireflies. China and USA is the most highest collaboration among others countries in fireflies research. This research can help researchers or academics who are new to firefly research by providing information on which publications and authors to refer when performing firefly research.